Model Pengajaran Tuhan Yesus: Pendekatan Pembelajaran Berbasis Nilai dan Kasih - Vriska Friyanti; Lasmauli Gurning (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This paper discusses the teachings of the Lord Jesus through a values ​​and love-based approach. Based on my understanding, the teachings of the Lord Jesus have a very important role in the methods that will be used by teaching staff or teaching staff. This paper analyzes the teachings of the Lord Jesus, recorded in the Gospels, not only as spiritual teachings, but also as a moral and pedagogical guide for educators. At the discussion stage, the New Testament shows Jesus as an extraordinary teacher, providing an important example in his life in the world. He not only demonstrated effectiveness and efficiency in his teaching model, but also had specific goals and strategies. His way of teaching is very unique and creative, using practical illustrations from everyday life so that it is easy for everyone to understand. The conclusion of this paper is that the Lord Jesus' teaching model provides a solid foundation for educational practice centered on values ​​and love. The principles he taught are not only relevant in a spiritual context, but also have powerful applications in modern education.